2010
DOI: 10.2353/ajpath.2010.100174
|View full text |Cite
|
Sign up to set email alerts
|

An Omega-3 Fatty Acid-Enriched Diet Prevents Skeletal Muscle Lesions in a Hamster Model of Dystrophy

Abstract: Currently, despite well-known mutational causes, a universal treatment for neuromuscular disorders is still lacking, and current therapeutic efforts are mainly restricted to symptomatic treatments. In the present study, ␦-sarcoglycan-null dystrophic hamsters were fed a diet enriched in flaxseed-derived 3 ␣-linolenic fatty acid from weaning until death. ␣-linolenic fatty acid precluded the dystrophic degeneration of muscle morphology and function. In fact, in dystrophic animals fed flaxseed-derived ␣-linolenic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
1
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 43 publications
1
26
1
2
Order By: Relevance
“…EPA treatment has also been reported to prevent arthritis‐induced reductions in gastrocnemius muscle weight in rats following administration of Freund's adjuvant, concomitant with the normalization of atrogin‐1/MAFbx and MuRF1 gene expression . Moreover, dystrophic hamsters fed a diet enriched in the PUFA α‐linolenic acid (ALA) (C18:3(n‐6)) exhibited improvements in muscle morphology and function, including enlarged myofibres . In accord with these findings, omega‐3 and omega‐6 PUFAs have also been shown to increase phosphorylation of p70S6K1 at Thr389, indicative of its increased activity, during myogenic differentiation of L6 myocytes .…”
Section: Fatty Acid Modulation Of Skeletal Muscle Mass and Functionmentioning
confidence: 79%
See 1 more Smart Citation
“…EPA treatment has also been reported to prevent arthritis‐induced reductions in gastrocnemius muscle weight in rats following administration of Freund's adjuvant, concomitant with the normalization of atrogin‐1/MAFbx and MuRF1 gene expression . Moreover, dystrophic hamsters fed a diet enriched in the PUFA α‐linolenic acid (ALA) (C18:3(n‐6)) exhibited improvements in muscle morphology and function, including enlarged myofibres . In accord with these findings, omega‐3 and omega‐6 PUFAs have also been shown to increase phosphorylation of p70S6K1 at Thr389, indicative of its increased activity, during myogenic differentiation of L6 myocytes .…”
Section: Fatty Acid Modulation Of Skeletal Muscle Mass and Functionmentioning
confidence: 79%
“…Notably, these growth suppressing actions have been linked to reduced levels of cyclin E and CDK2, proteins which play a critical role in cell cycle progression, as well as suppressed activation of ERK1/2, a mitogen‐activated protein kinase implicated in promoting cell growth and division . In contrast, feeding dystrophic δ‐sarcoglycan deficient hamsters a diet enriched in ALA (an omega‐3 PUFA) was demonstrated to increase satellite cell proliferation and differentiation in EDL muscle, concomitant with improved muscular histology . Notably, these beneficial responses coincided with the ability of ALA to increase the proportion of α‐MHC positive myofibres in skeletal muscle of dystrophic hamsters, along with a reduction in β‐MHC expression, thereby contributing to the preservation of a more physiological α/β MHC ratio.…”
Section: Role Of Unsaturated Fatty Acids In Maintaining Skeletal Muscmentioning
confidence: 99%
“…Hence, ALA protective effect was studied in rats using a well-known experimental model of infarct-like myocardial damage obtained by repeated injections of ISO 22,23 . The enrichment of ALA was achieved employing an already validated diet, which was used to address the role of ALA mediated protection in cardiomyocytes and hamsters with genetic cardiomyopaties 18,20,21 . Here, we estimate that 2.85 g/day of ALA was assumed by each rat.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, we assessed the triggering of pro-survival pathways in an in vitro model (H9c2 rat cardiomyocytes). Then, we studied the effects of an ALAenriched diet 18,20,21 in adult Wistar rats, which were repeatedly injected with isoproterenol (ISO).…”
Section: Introductionmentioning
confidence: 99%
“…Recent human studies have found that supplementation with long chain n-3 PUFA increases rates of protein synthesis and augments the muscle protein anabolic response, and may also attenuate acute muscle loss (cachexia) (236)(237)(238)(239)(240)(241) . One small observational study found a negative association with appendicular lean mass and saturated fat, and a comprehensive study of dietary fat composition and muscle mass found positive associations with the PUFA:SFA ratio and negative associations with saturated and trans fatty acids (15,81) .…”
Section: Dietary Fat Compositionmentioning
confidence: 99%